KONTEKSTUALISASI HUKUM ISLAM RAMAH LINGKUNGAN - Arief Aulia Rachman (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2011)
The term of environmentally-friendly religion, environmentally-friendly education andenvironmentally-friendly culture is a form of seriousness in the face of environmental crisesand destructions that occurred lately. Therefore, this paper discusses environmental issuesin the perspective of Islamic law as a form of appreciation and anxiousness to theenvironmental problems that occurred and still have not been found the solution. In generalIslam suggests humans to treat and preserve this natural ecosystem in the best way andwith much care. It is as a mandate manifestation of Allah entrusted to man as his caliph.